Assessment of Endothelial Dysfunction: The Role of Symmetrical Dimethylarginine and Proinflammatory Markers in Chronic Kidney Disease and Renal Transplant Recipients. Issue 3 (26th August 2013) - Memon, Lidija; Spasojevic-Kalimanovska, Vesna; Bogavac-Stanojevic, Natasa; Kotur-Stevuljevic, Jelena; Simic-Ogrizovic, Sanja; Giga, Vojislav; Dopsaj, Violeta; Jelic-Ivanovic, Zorana; Spasic, Slavica
Abstract : Objectives . The study was designed to evaluate associations between symmetric dimethylarginine (SDMA), inflammation, and superoxide anion (O 2 ∙ - ) with endothelial function and to determine their potential for screening of endothelial dysfunction in patients with chronic kidney disease (CKD) and renal transplant (RT) recipients. Materials and Methods . We included 64 CKD and 52 RT patients. Patients were stratified according to brachial artery flow-mediated dilation (FMD). Results . Logistic regression analysis showed that high SDMA and high sensitive C-reactive protein (hs-CRP) were associated with impaired FMD in CKD and RT patients, after adjustment for glomerular filtration rate. The ability of inflammation, SDMA, andO 2 ∙ - to detect impaired FMD was investigated by receiving operative characteristic analysis. Hs-CRP (area under the curves (AUC) = 0.754, P < 0.001 ), IL-6 (AUC = 0.699, P = 0.002 ), and SDMA (AUC = 0.689, P = 0.00 7 ) had the highest ability to detect impaired FMD. SDMA in combination with inflammatory parameters and/orO 2 ∙ - had better screening performance than SDMA alone. Conclusions . Our results indicate a strong predictable association between hs-CRP, SDMA, and endothelial dysfunction in CKD patients and RT recipients. The individual marker that showed the strongest discriminative ability for endothelial dysfunction is hs-CRP, but its usefulness as a discriminatory marker for efficient diagnosis of endothelial dysfunction should be examined in prospective studies.